Challenges and perspectives for tomato moth management (Research, Society and Development, 2022)
The tomato (Solanum lycopersicum L.) is a cosmopolitan plant of great worldwide importance and its cultivation is present in several tropical and subtropical countries. However, the occurrence of the tomato leafminer [Tuta absoluta (Meyrick)] can cause damages of up to 100% in crops. This insect forms galleries in leaves, stems, flowers and fruits of the tomato plant, during the entire phenological development. In recent years, this pest has caused many losses in tomato crops due to the selection of populations resistant to diamides, the main insecticide molecule used to control the tomato pinworm.The objective of this work was to combine data from multiple studies on T. absoluta in order to establish, in the current scenario, possible solutions and perspectives for the management of this pest, using Google Scholar as a search tool. The tomato pinworm is currently a matter of concern in several producing countries, due to its high potential for infestation, adaptation and resistance to insecticides (Diamides). Making the use of biological control methods based on the use of predators (Mirids), parasitoids (Trichogramma), entomopathogens and pheromone traps, important tools for the sustainable management of this pest. The study concludes that biological control methods may be important for an integrated management of pleats in view of their resistance to insecticides. Making it essential to know the biology and behavior for better results in the management and monitoring of the tomato pinworm.